On Applicability of a Miniaturised Laser Ablation Time of Flight Mass Spectrometer for Trace Elements Measurements. (15th February 2012) - Tulej, Marek; Riedo, Andreas; Iakovleva, Maria; Wurz, Peter
Abstract : We present results from mass spectrometric analysis of NIST standard materials and meteoritic samples conducted by a miniaturised laser ablation mass spectrometer designed for space research. The mass analyser supports investigation with a mass resolution (m / Δ m ) ≈ 500–600 and dynamic range within seven decades. Nevertheless, to maintain an optimal spectral quality laser irradiances lower than 1 GW/cm 2 are applied so far which results in a spread of RSC values. To achieve the quantitative performance of mass analyser, various effects influencing RSC factors have to be investigated. In this paper we investigate influence of laser irradiance, sampling procedure and plasma chemistry on the quantitative elemental and isotopic analysis. The studies indicate necessity for accurate control of laser characteristics and acquisition procedure. A relatively low irradiance applied causes a negligible sample damage and allows for accumulation of large number of waveforms from one sample location. The procedure yields statistically well averaged data and allows a sensitive in-depth analysis. The quantitative analyses of isotopic composition can be performed with accuracy and precision better as 1% and 2%, for isotopic patterns of elements and clusters, respectively. The numerical integration methods would be preferred to achieve more accurate results. The measurements of Allende sample yield detection of Pb isotopic pattern, nevertheless cluster species are readily observed in spectrum and make the elemental analysis of other trace elements difficult due to isobaric interferences. These detections are of a considerable interest because of possible application of the instrument for in situ elemental and isotopic analysis and radiometric dating of solids.